LIABILITY RULE PRACTICES AMIDST THE PROPERTY RULE OF INDONESIAN CAPITAL MARKET - Adiwarman, Adiwarman (UI Scholars Hub, 2022)
Shareholder protection is the most important legal issue in capital market law. Conflict of interest is one of the corporate actions in the capital market. The property rule requires independent shareholders’ approval for conflicts of interest transactions. The property rule paradigm empowers independent shareholders in the company’s decision-making process. In practice, listed companies violate the property rule and are subject to sanctions, but the rights of shareholders will be reduced due to fines imposed by the capital market authorities. A normative method is used to answer the problem of how does Indonesia enforce the conflict of interest rule in order to protect the independent shareholders? OJK enforces the law and on violations of conflicts of interest transactions. In this perspective, the liability rule principle emerges to execute the conflict of interest transaction. Recommendations from the results of this study: 1) OJK strictly asks the listed company previously to have approval from independent shareholders for conflict of interest transactions. If it does not harm the listed company, then OJK exposes administrative sanctions without a fine. For the repetitive conflict of interest transactions, OJK can give administrative sanctions with a fine to the listed company. 2) If a conflict of interest causes a loss, then OJK does not stop at enforcing the conflict of interest transactions rule, but should also include the implementation of the liability rule and compensation to shareholders. 3) The fairness of conflict of interest transactions is the determinant of the validity of the transaction. Profit and loss analysis and market price can be applied to assess the fairness of the conflict of interest transaction. 4) The Court becomes a forum to determine the value of compensation for detrimental conflicts of interest transactions.